Expansão do agronegócio canavieiro no sul goiano e os efeitos na produção de alimento - Pedro Dias Mangolini Neves; Marcelo Rodrigues Mendonça (Confins)
The south region of Goiás has been transformed since the 21st century into one of the areas with the greatest expansion of cultivated land and sugarcane production, based on a strategic modification of the sugarcane agribusiness capital with the State consent. In this way, to understand the dynamics of this territory that favor the expansion of sugarcane agroindustry through programs and public policies, soil and climatic conditions, water availability, fertile soils, considering the mapping proposed by the Agroecological Zoning of Sugarcane (MANZATTO et al. 2009) corresponds to the objective of this research. In addition, it is intended to demonstrate that there is a decrease in the production of food, especially rice, cassava, wheat and dairy production in the South of Goiás concomitantly with the expansion of the sugar cane agribusiness. This research points to a contradiction existing in the literature of this subject that consider the expansion of sugarcane in the South of Goiás as a result of the retraction of the production of monocultures such as soybean and corn and the production of livestock. In the meantime, it is considered that the State must intervene in the food production as well as they currently intervene in the production of commodities with financing programs, fiscal incentives, infrastructure construction and protectionism, for sovereignty and food security.